2022
DOI: 10.1093/ofid/ofac395
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity, Risks, and Morbidity From Varicella-Zoster Virus Infections in an Adult PWH Cohort From 2000–2020

Abstract: Background Varicella-zoster virus (VZV) infection disproportionately affects people with HIV (PWH) primarily presenting as Herpes Zoster. However, VZV seroprevalence, its association with zoster, and clinical outcomes, remain understudied in era of modern antiretroviral therapy (ART). We assessed VZV seroprevalence, rates of VZV illness, and associated healthcare costs in a large PWH cohort over 20 years. Methods We performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In people living with HIV, herpes zoster can be categorized as an opportunistic infection. In this population, its occurrence is not only more prevalent but also more likely to be accompanied by complications compared to the general population, even among individuals who are receiving effective ART [11,12]. Although limited data are available on the current seroprevalence of VZV infection in PLWH, some studies indicate a prevalence of VZV-positive serological patients of approximately 95% [13].…”
Section: Discussionmentioning
confidence: 99%
“…In people living with HIV, herpes zoster can be categorized as an opportunistic infection. In this population, its occurrence is not only more prevalent but also more likely to be accompanied by complications compared to the general population, even among individuals who are receiving effective ART [11,12]. Although limited data are available on the current seroprevalence of VZV infection in PLWH, some studies indicate a prevalence of VZV-positive serological patients of approximately 95% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Likely due to high rates of pneumococcal vaccine uptake (free as government funded) by our PWH we had only one case of S. pneumoniae meningitis. Similarly, low use of zoster vaccines (unfunded) may account for several avoidable VZV CNS infections [30]. Due to small numbers, particularly of non-AIDS defining neurologic infections trends in incidence rate over time may be difficult to interpret, also comparative analytics were not stratified by AIDS and non-AIDS defining neurologic infections.…”
Section: Discussionmentioning
confidence: 99%
“…HZ is caused by a variety of diseases that affect immunity, and its incidence increases with decreasing immune levels [ 41 , 42 ]. Hawkins et al [ 43 ] and Zou et al [ 44 ] found that PLWH with lower CD4 and unsuppressed HIV-1 RNA have the higher risk of HZ. Therefore, we speculate that HZ represents a manifestation of immune suppression, to some extent.…”
Section: Discussionmentioning
confidence: 99%